Pengaruh Electronic Word of Mouth (EWOM) Terhadap Brand Image, Trust dan Keputusan Berkunjung ke Kampung Tridi Malang - Monica Yohana Putri Wiryokusumo; Agung Suryawan Wiranatha; I Gusti Ayu Oka Suryawardani (JURNAL MASTER PARIWISATA, 2021)
Electronic word of mouth (EWOM) is quite effective in increasing the decision to visit tourist destinations. Indirectly, electronic word of mouth has an important role in forming a brand image, so there is a need for a good brand image to increase trust so that tourist visits can increase. The purpose of this research are to (1) to analyze the effect of the Electronic Word of Mouth on brand image, trust and the decision to visit in Kampung Tridi Malang, (2) to analyze the influence of brand image on the decision to visit in Kampung Tridi Malang, and (3) to analyze the effect of trust on decisions. visited Kampung Tridi Malang. This study uses SEM (Structural Equation Modeling) analysis using the SmartPLS 3.0 student version software. The data collection instrument used a questionnaire with 100 respondents. The distribution of questionnaires was carried out by purposive sampling to domestic tourists. The results of this research indicate that 1) electronic word of mouth has a significant effect on brand image, (2) electronic word of mouth has a significant effect on trust, (3) electronic word of mouth has a significant effect on visiting decisions, (4) brand image has a significant effect on trust. decision to visit and (5) trust has a significant effect on the decision to visit 6) electronic word of mouth has a significant effect on the decision to visit through brand image 7) electronic word of mouth has a significant effect on the decision to visit through trust. The influence of EWOM on the decision to visit is quite strong so that it can be considered for the managers of Kampung Tridi Malang to further develop marketing using social media. Keywords: Electronic Word of Mouth, Brand Image, Trust, Visit Decision, Kampung Tridi Malang